EFEKTIVITAS MEDIA PEMBELAJARAN MATEMATIKA BERBASIS PERMAINAN EDUKATIF ULAR TANGGA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMA DI ANGKOLA BARAT - Simbolon, Tara Mashuri; Ardiana, Nunik; Harahap, Muhammad Syahril (JURNAL MathEdu (Mathematic Education Journal), 2026)
The research conducted aims to determine the effectiveness of educational game-based mathematics learning media snakes and ladders to improve mathematical problem-solving skills of class X-2 students of SMA Negeri 1 Angkola Barat. The research method used in this study is using classical completeness. The subjects in this study came from 3 validators, as well as class X-2 students. The data collection technique used was using a questionnaire validation question and test for effectiveness testing. The results of the test question instrument validation analysis obtained a total percentage of achievement of 90% with the category "Very Valid". The results of the effectiveness data analysis obtained an overall average value of 75.45 with the category "Complete" and a percentage of completeness of 64.70% with the category "Effective". Based on the results obtained, it can be concluded that the resulting learning media is valid, practical, and effective.